'Transitions in Context: Making Peace in 1814 – 1815; 1918 – 1920; 1945 – 1955ʹ. Issue 2 (3rd April 2021) - Langhorne, Richard
ABSTRACT: Frequently, peace settlements mark moments of systemic change in international politics. The object of this article is to examine how far these three major European peace settlements of the modern period – 1814–15, 1918–20 and 1945-55 – represented the contemporary political and diplomatic responses to the urgent needs that the end of a general war inevitably brings. It argues that, with the exception of the Vienna settlement, often the urgency of the situation at the end of the war was itself the consequence of underlying conditions which were so profound as to be immutable at any particular moment and immune from any short-term political interventions. Too much should never be expected of formal peace settlements.